Influența grupurilor de interese în activitatea Parlamentului român* (The influence of interest groups on the activity of the Romanian Parliament) - Cosmin DIMA (Polis: Revista de Stiinte Politice, 2016)
The article investigates how interest groups influence the Parliament’s work. These are directly interested in the legislative process since is the last ”stronghold” where can intervene to change legislation in line with the interests they represent. Within the parliamentary committees, where the legislative activity is getting on, the interaction between interest groups and committees’ members leads, sometimes, to the modification of legislative process.